Isolation and characterization of human mesenchymal stem cells from gingival connective tissue. (17th September 2014) - Jin, S. H.; Lee, J. E.; Yun, J‐H.; Kim, I.; Ko, Y.; Park, J. B.
<x xml:space="preserve">Abstract</x> Background and Objective The main purpose of this study was to isolate and characterize gingival connective tissue‐derived mesenchymal stem cells (GMSCs). The secondary purpose was to present a modified isolation method for the GMSCs. Material and Methods Collected healthy gingival tissue samples were de‐epithelialized and minced into small fragments. The tissues were digested by dispase and collagenase IV for 30 min. The first digested cell suspension was discarded, and then additional digestion was performed to the remaining cells in the same solution for 90 min. The isolated cells from gingiva was incubated in 37°C humidified condition and observed by inverted microscope. Cytoskeletal morphology was evaluated by phalloidin immunofluorescence. Potency of the cells was tested by colony‐forming unit fibroblast assay. GMSCs were characterized by osteogenic, adipogenic and chondrogenic differentiation, and flow cytometric, immunofluorescence analysis. Results GMSCs showed spindle‐shaped, fibroblast‐like morphology, colony‐forming abilities, adherence to plastic and multilineage differentiation (osteogenic, adipogenic, chondrogenic) potency. GMSCs expressed CD44, CD73, CD90 and CD105, but did not express CD14, CD45, CD34 and CD19 in flow cytometry. Expression of stem cell markers (SSEA‐4, STRO‐1, CD146, CD166 and CD271) and a mesenchymal marker (vimentin) were observed by immunofluorescence. Conclusions In conclusion, we isolated and characterized stem cells from human gingival connective tissue with modified protocol. GMSCs showed multipotency with high proliferation and characteristics of mesenchymal stem cells. GMSCs are promising sources for tissue engineering and may be obtained during routine procedures under local anesthesia. Further research is needed to evaluate the potential of GSMCs' proliferation and cryopreservation.